2016
DOI: 10.1038/ncomms11567
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa elastase cleaves a C-terminal peptide from human thrombin that inhibits host inflammatory responses

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen known for its immune evasive abilities amongst others by degradation of a large variety of host proteins. Here we show that digestion of thrombin by P. aeruginosa elastase leads to the release of the C-terminal thrombin-derived peptide FYT21, which inhibits pro-inflammatory responses to several pathogen-associated molecular patterns in vitro and in vivo by preventing toll-like receptor dimerization and subsequent activation of down-stream signalling pathways.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 41 publications
9
64
0
Order By: Relevance
“…5). As previously reported, subsequent proteolysis leads to formation of smaller TCPs of about 2 kDa with antiendotoxic functions (10,14,15) (Fig. 5).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…5). As previously reported, subsequent proteolysis leads to formation of smaller TCPs of about 2 kDa with antiendotoxic functions (10,14,15) (Fig. 5).…”
Section: Discussionmentioning
confidence: 53%
“…5). Interestingly, P. aeruginosa "hijacks" this mechanism by release of bacterial elastase, which cleaves out a TCP of 21 aa, thereby enabling modulation and circumvention of host responses (14). In many aspects, such TCPs act as "classical" host defense peptides like LL-37 (26), which also binds to LPS, leading to inhibition of NF-κB activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, elastases cleave complement components and also elastin, collagen, IgG, mucin, and surfactant proteins to escape from phagocytosis and clearance [46]. Pseudomonas proteases can mimic the activity of neutrophil elastase by cleaving peptides from host thrombin that inhibits inflammatory responses [47]. …”
Section: Qs-regulated Factors That Impact P Aeruginosa Communities Amentioning
confidence: 99%
“…In addition, P. aeruginosa elastase is known to lead to degradation of pro-inflammatory cytokines such as IL-6 or IL-8 to avoid host immune defense (37). A recent report also showed that thrombin cleaved by P. aeruginosa elastase attenuated TLR-mediated pro-inflammatory responses (38). In correlation with these studies, our results clearly demonstrate that P. aeruginosa proteases degrade inflammasome components including caspase-1 and ASC, as well as pro-inflammatory cytokines in the extracellular space (Figure 9).…”
Section: Discussionmentioning
confidence: 97%